Evaluation of (99m)Tc-HYNIC-MPG as a novel SPECT radiotracer to detect EGFR-activating mutations in NSCLC - Xiao, Zunyu (Oncotarget, 2017)
Tyrosine kinase inhibitors (EGFR-TKIs) targeting the epidermal growth factor receptor (EGFR) have been used in non-small cell lung carcinoma (NSCLC) for years with promising results, in particular in patients with activating mutations in the EGFR kinase domain (exon 19 E746-A750 deletion or exon 21 L858R point mutation). However, despite their great success in the clinic, a significant number of patients do not respond to EGFR-TKIs, such as those carrying the L858R/T790M mutation or EGFR wild type. Thus, detecting the EGFR mutation status before EGFR-TKIs therapy is essential to ensure its efficacy. In this study, we report a novel SPECT tracer (99m)Tc-HYNIC-MPG that binds specifically to activating mutant EGFR and which could therefore be used to noninvasively select patients sensitive to EGFR-TKIs. We evaluated the capacity of (99m)Tc-HYNIC-MPG in detecting EGFR-activating mutations both in vitro and in vivo using four human NSCLC cell lines (PC9, H1975, H358 and H520). (99m)Tc-HYNIC-MPG had significantly higher accumulation in PC9 tumor cells when compared to H1975, H358 and H520 tumors cells, which may be due to the activating mutations (exon 19 deletion) in EGFR tyrosine kinase domain in PC9 cells. Thus, (99m)Tc-HYNIC-MPG SPECT imaging may be used to identify NSCLC tumors with a potential high response rate to EGFR-TKIs.